RELATIONSHIP BETWEEN CAREER SHOCKS AND EMPLOYEE WORKPLACE BEHAVIOUR - Ibironke Ibironke; Adekunle Emmanuel; Adegbite; Waliu Mulero; Dagunduro; Adebukola Olufunke (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
There have been different studies to examine the effect of career-related issues such as career-planning, career-management, on employees' workplace-related behavior, but the concept of career shocks is not covered especially in the local context of Nigeria to establish how and when shock trigger employees’ behavioural responses or workplace outcomes career. This study examined the relationship between career shock dimensions (positive and negative career shocks) and employee workplace behaviour. The objectives of the study considered the relationship between positive career shock and employees’ workplace behaviours as well as negative career shock and employees’ workplace behaviours. The conservation of resource theory was adopted for this work. Using the survey research design. A population of 124 employees from National Postgraduate Medical College of Nigeria was used for the study and a sample size of 95 participants was determined using Taro Yamane’s formula. However, the data analysis was based on 89 valid responses that were received from the respondents. Data was collected with the use of a questionnaire. The Pearson’s Product Correlation was used in testing the hypotheses. The result of the analyses revealed a positive correlation for both career shocks on employees' workplace behaviour. In line with this findings, it was recommended that organisations should endeavor to consider policies and organisational structures to help employees manage career shocks well.